2018
DOI: 10.5658/wood.2018.46.6.748
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Methyl Methacrylate-Impregnated Wood to Subterranean Termite Attack

Abstract: Timber from fast-growing tree species is susceptible to by biodeterioration attack, particularly subterranean termites. Impregnation with methyl methacrylate (MMA) potentially increases wood resistance to subterranean termite attack. Four wood species, namely sengon (Falcataria moluccana), jabon (Anthocephalus cadamba), mangium (Acacia mangium), and pine (Pinus merkusii), were impregnated with MMA, and samples of untreated and imidacloprid-preserved wood were prepared for comparison purposes. Small stakes, siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(5 citation statements)
references
References 18 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…These subterranean termites are members of the Termitidae family, except Schedorhinotheres sp., a member of the family Rhinotermitidae. In the research of Hadi et al (2018) at the same research site, where this research was conducted, the type of termite found was the Coptotermes curvignathus.…”
Section: Identification and Distribution Of Subterranean Termite Speciesmentioning
confidence: 99%
“…These subterranean termites are members of the Termitidae family, except Schedorhinotheres sp., a member of the family Rhinotermitidae. In the research of Hadi et al (2018) at the same research site, where this research was conducted, the type of termite found was the Coptotermes curvignathus.…”
Section: Identification and Distribution Of Subterranean Termite Speciesmentioning
confidence: 99%
“…In this study, MMA and styrofoam were used as binders OPTB-particleboard. The use of MMA is expected to improve the quality of OPTB-particleboard, especially its durability as previous other studies carried out [18,19]. In contrast, the use of styrofoam is expected to improve the quality of OPTBparticleboard, especially the physical and mechanical properties of the OPTB-particleboard and help reduce styrofoam waste in the environment [13].…”
Section: Global Forest Journalmentioning
confidence: 88%
“…Hasman et al (2019) reported that unfavorable environmental conditions can cause termite death. Previous research stated that the research results showed that the average air temperature at the research location was 25.15 ± 1.46℃ with humidity 75%-90%, indicating optimal termite feeding behavior, especially for subterranean termites from the Termitidae and Rhinotermitidae families such as Macrotermes sp., Microtermes sp., Capritermes sp., Schedorhinotermes sp., and C. curvignathus (Arinana et al, 2022;Hadi et al, 2018). In addition, Tampubolon et al (2015) explained that in addition to environmental conditions, the nature of cannibalism in termites also affects termite mortality.…”
Section: Mortality Of Subterranean Termitesmentioning
confidence: 99%